1988
DOI: 10.1093/oxfordjournals.aje.a115087
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Depressive Symptoms: The Nhanes I Epidemiologic Follow-Up Study

Abstract: The relation between self-reported physical activity and depressive symptoms was analyzed for 1,900 healthy subjects aged 25-77 years in the Epidemiologic Follow-up Study (1982-1984) to the first National Health and Nutrition Examination Survey (NHANES I). Depressive symptomatology as measured by the Center for Epidemiologic Studies Depression Scale (CES-D) was examined by sex and race in relation to recreational physical activity and physical activity apart from recreation, controlling for age, education, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
283
8
19

Year Published

1991
1991
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 507 publications
(336 citation statements)
references
References 0 publications
26
283
8
19
Order By: Relevance
“…Four major classes of attrition have been identified in the literature: an eligible participant declines to enter the study at its initialization, a participant declines to complete a questionnaire at a subsequent follow-up, there is nonresponse due to incapacity or death, or researchers fail to relocate a participant for a follow-up wave. Previously, large epidemiologic studies found different predictors for each of these reasons for attrition 17,18 . The design of the Mater-University of Queensland Study of Pregnancy did not allow us to easily distinguish whether nonresponse at a follow-up wave was caused by participant refusal, researchers not being able to relocate a participant, or because of participant incapacity.…”
Section: Discussionmentioning
confidence: 99%
“…Four major classes of attrition have been identified in the literature: an eligible participant declines to enter the study at its initialization, a participant declines to complete a questionnaire at a subsequent follow-up, there is nonresponse due to incapacity or death, or researchers fail to relocate a participant for a follow-up wave. Previously, large epidemiologic studies found different predictors for each of these reasons for attrition 17,18 . The design of the Mater-University of Queensland Study of Pregnancy did not allow us to easily distinguish whether nonresponse at a follow-up wave was caused by participant refusal, researchers not being able to relocate a participant, or because of participant incapacity.…”
Section: Discussionmentioning
confidence: 99%
“…Following samples of non-depressed subjects over time, the general finding is that physically active people have a reduced tendency to develop depression (8,9). Although these findings are more compelling, they cannot rule out the potential for self-selection.…”
Section: Preventionmentioning
confidence: 99%
“…The reliability of these answers has not been tested, and the indirect validity of these data in the NHANES I study is limited. 41 The usefulness and limitations of simplified physical activity questionnaires have been discussed elsewhere. 42 -43 Finally, the relatively small numbers of black men and women reduced the power of the study to detect associations in these groups.…”
Section: -21mentioning
confidence: 99%